"When they are all grown, I will tell them": Experience and perceptions of parental self-disclosure of HIV status to children in Nairobi, Kenya - Cyrus Mugo; Olivia Firdawsi; Jiayu Wang; Irene N. Njuguna; Dalton C. Wamalwa; Jennifer A. Slyker; Grace C. John-Stewart; Gabrielle O'Malley; Anjuli D. Wagner (BMC, 2023)
Abstract Background There is mixed evidence on the influence of self-disclosure of one's HIV status on mental health, health behaviours and clinical outcomes. We studied the patterns of self-disclosure among parents living with HIV, and factors that influence parental disclosure. Methods This mixed-methods study was among adults in HIV care participating in a study assessing the uptake of pediatric index-case testing. They completed a survey to provide demographic and HIV-related health information, and assess self-disclosure to partners, children and others. We ran generalized linear models to determine factors associated with disclosure and reported prevalence ratios (PR). Eighteen participants also participated in in-depth interviews to explore perceived barriers and facilitators of self-disclosure to one's child. A content analysis approach was used to analyze interview transcripts. Results Of 493 caregivers, 238 (48%) had a child ≥ 6 years old who could potentially be disclosed to about their parent's HIV status. Of 238 participants, 205 (86%) were female, median age was 35 years, and 132 (55%) were in a stable relationship. Among those in a stable relationship, 96 (73%) knew their partner's HIV status, with 79 (60%) reporting that their partner was living with HIV. Caregivers had known their HIV status for a median 2 years, and the median age of their oldest child was 11 years old. Older caregiver age and older first born child's age were each associated with 10% higher likelihood of having disclosed to a child (PR: 1.10 [1.06-1.13] and PR: 1.10 [1.06-1.15], per year of age, respectively). The child's age or perceived maturity and fear of causing anxiety to the child inhibited disclosure. Child's sexual activity was a motivator for disclosure, as well as the belief that disclosing was the "right thing to do". Caregivers advocated for peer and counseling support to gain insight on appropriate ways to disclose their status. Conclusions Child's age is a key consideration for parents to disclose their own HIV status to their children. While parents were open to disclosing their HIV status to their children, there is a need to address barriers including anticipated stigma, and fear that disclosure will cause distress to their children.